Exercise intensity conversion from a bicycle ergometer to a treadmill - Bunc, V; Heller, J (The Journal of sports medicine and physical fitness, 1991)
In the evaluation of the general functional fitness and/or work capacity of subjects for the purpose of exercise diagnostics, physical fitness enhancement in untrained healthy subjects or sportsmen and exercise rehabilitation of patients, two types of ergometers are generally used: a bicycle ergometer and a treadmill. To facilitate the conversion of results of functional examinations made in the laboratory to field conditions, where, as a rule, physical activity is performed, the intensity of exercise assessed on the bicycle ergometer must be converted to that on a treadmill and vice versa. Measurements on a bicycle ergometer and treadmill in differently trained groups of men can be supplemented with data from the literature to develop a general equation which relates exercise intensity on the bicycle ergometer P (W.kg-1) and running speed on the treadmill v (km.h-1) as v = 3.544.P +/- 0.625. In the submaximal range of exercise intensities (20-80% of maximal aerobic power) this relationship is independent on the training status, age, body weight, strength and speed capacity of the subjects examined. The above equation may be used in the submaximal exercise intensity range with a maximum error of about 12% or less.
Keywords: Physical Fitness; zátěžový test; energetický metabolismus; Physical Education and Training; Energy Metabolism; tělesná výchova; tělesná výkonnost; Humans; Oxygen Consumption; fyziologická adaptace; Exercise Test; lidé; spotřeba kyslíku; Adaptation, Physiological